Pyroptosis in development, inflammation and disease - Pan, Yuhong; Cai, Wenjun; Huang, Juan; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Jia, Renyong (Frontiers in Immunology, 2022)
In the early 2000s, caspase-1, an important molecule that has been shown to be involved in the regulation of inflammation, cell survival and diseases, was given a new function: regulating a new mode of cell death that was later defined as pyroptosis. Since then, the inflammasome, the inflammatory caspases (caspase-4/5/11) and their substrate gasdermins (gasdermin A, B, C, D, E and DFNB59) has also been reported to be involved in the pyroptotic pathway, and this pathway is closely related to the development of various diseases. In addition, important apoptotic effectors caspase-3/8 and granzymes have also been reported to be involved in the induction of pyroptosis. In our article, we summarize findings that help define the roles of inflammasomes, inflammatory caspases, gasdermins, and other mediators of pyroptosis, and how they determine cell fate and regulate disease progression.